Equivalent characterization of resilient rotation symmetric functions with q number of variables over GF(p) - Jiao DU; Shan-qi PANG; Qiao-yan WEN; GJie ZHAN (Tongxin xuebao)
Baesd on the property of the l-value support tables of the resilient rotation symmetric functions (RSF) with q number of variables, an equivalent characterization on the resilient RSF with q number of variables is derived. It is proved that construction of the resilient RSF with q number of variables are equivalent to solve an equation system. At last, the count of resilient RSF with q number of variables are represented by using all the solutions of the equation system. Key words: rotation symmetric functions; l-value support table; orthogonal arrays; resilient functions